Digitalisasi Pembelajaran Bahasa Arab: Gerakan Peningkatan Antusias Santri dan Narasi Adaptasi Pesantren Terhadap Perkembangan Teknologi - Rasyidin Rasyidin; Radinal Mukhtar Harahap (Departement of Mathematics Education, 2024)
This report is a portrait of the digitalization of Arabic education at Pesantren Ar-Raudlatul Hasanah, which is conceived as a movement to increase students' enthusiasm for learning and institutional adaptation to technological developments and digitalization. This report based on on other research on personalized learning as a motivation for parents to send their children to Islamic boarding schools during Covid-19, this report encourages Islamic boarding schools to consider learning methods that appeal to millennial students. This article is prepared using field research methods to find that digitalizing Arabic learning can create presentation media in the form of PowerPoint that increases students' enthusiasm for learning. This finding is seen as a new scientifically proven story about the adaptation of Islamic boarding schools to current developments